WHAT MARKETING CAPABILITIES MATTER IN SERVICE DIGITALIZATION? A STRUCTURED ABSTRACT REVIEW - Melisa Maria Gosal; Daniel Peterson Silaban (Jurnal Comparative: Ekonomi dan Bisnis, 2026)
Â Digital transformation is reshaping competition in service industries by shifting emphasis from mere technology adoption to the development of marketing capabilities. However, existing research is fragmented and lacks a cross-sector perspective on how digital service marketing capabilities evolve. This study investigates the core capabilities emerging across service sectors and how they are strategically developed. Using a qualitative systematic literature review of 22 Scopus-indexed articles published between 2021 and 2026, the research applies abstract-based thematic analysis. Five key capabilities are identified: communication, customer interaction, platform ecosystem management, analytics, and service experience design. The findings also reveal sector-specific variations across platform, tourism, and banking industries. Importantly, the evolution of these capabilities occurs through gradual capability building and integration rather than through isolated technology adoption. The study concludes that long-term competitiveness in digital service environments depends on strategically developing and integrating marketing capabilities, not simply implementing digital tools alone for sustainable future growth.